2023
DOI: 10.3390/healthcare11131812
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT and the Future of Digital Health: A Study on Healthcare Workers’ Perceptions and Expectations

Mohamad-Hani Temsah,
Fadi Aljamaan,
Khalid H. Malki
et al.

Abstract: This study aimed to assess the knowledge, attitudes, and intended practices of healthcare workers (HCWs) in Saudi Arabia towards ChatGPT, an artificial intelligence (AI) Chatbot, within the first three months after its launch. We also aimed to identify potential barriers to AI Chatbot adoption among healthcare professionals. A cross-sectional survey was conducted among 1057 HCWs in Saudi Arabia, distributed electronically via social media channels from 21 February to 6 March 2023. The survey evaluated HCWs’ fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…In a survey that evaluated healthcare professionals’ experiences with ChatGPT, a substantial majority (75.1%) indicated that they felt at ease with the prospect of incorporating ChatGPT into their healthcare routines, with 39.5% favouring using ChatGPT to assist in making medical decisions. 42 However, it must be emphasised that while LLMs can serve as valuable tools, they should complement rather than replace the expertise of qualified mental health professionals to ensure comprehensive and personalised care.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey that evaluated healthcare professionals’ experiences with ChatGPT, a substantial majority (75.1%) indicated that they felt at ease with the prospect of incorporating ChatGPT into their healthcare routines, with 39.5% favouring using ChatGPT to assist in making medical decisions. 42 However, it must be emphasised that while LLMs can serve as valuable tools, they should complement rather than replace the expertise of qualified mental health professionals to ensure comprehensive and personalised care.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of artificial intelligence and large language models in systematic reviews can also affect trust in health research. We anticipate that due to limited experience, evidence users will be more cautious about the application of studies that use such tools (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…OpenAI launched in last November 2022 the Chat Generative Pre-trained Transformer (ChatGPT) and revolutionised the approach in artificial intelligence to human–model interaction used for fields [ 4 ]. It was used in all areas: healthcare and management [ 5 , 6 , 7 , 8 , 9 ], aiding cosmetic orthognathic surgery consultation [ 10 ], revolutionising dental practices [ 8 , 11 , 12 ], medical scientific articles and education fields [ 6 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], support in disease diagnosis [ 24 ], revolutionising radiology, sonar imaging and writing assessment [ 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], pharmaceutical research and treatment [ 11 , 24 , 34 , 35 , 36 , 37 , 38 ], and navigating limitations and ethical considerations [ 18 , 19 , 31 , 35 , 38 , 39 ,…”
Section: Introductionmentioning
confidence: 99%